Togo - 2017 - Dirk Kohnert (Africa Yearbook Volume 14: Politics, Economy and Society South of the Sahara in 2017, 2018)
The demand for political alternance, initiated by institutional and electoral reforms, constituted the major contentious issue between the government and the challengers of the Gnassingbé regime throughout the year. Civil society organizations and representatives of the Christian church supported the demands of the opposition. The protest of the notorious divided opposition took a new momentum since August with the lead by a hitherto hardly known opposition party and its charismatic leader, Tikpi Atchadam. He organized huge demonstrations of all the 14 opposition parties in the second half of the year which put the government progressively under pressure. Foreign affairs were dominated by the impact of increased aid by the international donor community. Socio-economic development was marked by diminishing human development and economic freedom. – – Die Forderung nach politischem Wandel, die durch institutionelle und Wahlreformen eingeleitet wurde, war das ganze Jahr über der größte Streitpunkt zwischen der Regierung und den Herausforderern des Gnassingbé-Regimes. Zivilgesellschaftliche Organisationen und Vertreter der christlichen Kirche unterstützten die Forderungen der Opposition. Der Protest der notorisch gespaltenen Opposition erhielt seit August unter der Führung einer bislang kaum bekannten Oppositionspartei und ihres charismatischen Führers Tikpi Atchadam neuen Schwung. Er organisierte in der zweiten Jahreshälfte große Demonstrationen aller 14 Oppositionsparteien, die die Regierung zunehmend unter Druck setzten. Die Außenpolitik wurde von den Auswirkungen der erhöhten Hilfeleistungen der internationalen Gebergemeinschaft dominiert. Die sozioökonomische Entwicklung war von abnehmender menschlicher Entwicklung und wirtschaftlicher Freiheit geprägt.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2017; domestic policy; foreign affairs; socio-economic development; period under review 2017